2007
DOI: 10.4161/psb.2.6.4789
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cyclic Nucleotide Signalling

Abstract: The presence of the cyclic nucleotides 3',5'-cyclic adenyl monophosphate (cAMP) and 3',5'-cyclic guanyl monophosphate (cGMP) in plants is now generally accepted. In addition, cAMP and cGMP have been implicated in the regulation of important plant processes such as stomatal functioning, monovalent and divalent cation fluxes, chloroplast development, gibberellic acid signalling, pathogen response and gene transcription. However, very little is known regarding the components of cyclic nucleotide signalling in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 26 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…At present, it is unclear what specific gene products encode the proteins responsible for synthesis and catabolism of cAMP in plants (22). Nonetheless, cAMP has been unequivocally documented to be present in plant cells (27,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, it is unclear what specific gene products encode the proteins responsible for synthesis and catabolism of cAMP in plants (22). Nonetheless, cAMP has been unequivocally documented to be present in plant cells (27,40).…”
Section: Discussionmentioning
confidence: 99%
“…PAMP Signaling to NO Mediated by Endogenous cNMP. Genes encoding enzymes that synthesize (adenylyl cyclase) and break down (cNMP phosphodiesterase) cAMP in plant leaves have not yet been identified (22); translational arrest of a specific gene has not been associated with altered level of cAMP in plants. In consideration of this point, we took a pharmacological approach to manipulate endogenous cAMP.…”
Section: Cnmp Cngcs and Immune Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Nevertheless, recent study shows the presence of cAMP and AC activity in several plant species. AC activity was reported in alfalfa and tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…17 For example, plant AC is closely associated with signaling cascade for pollen tube growth, 14 and cAMP have been shown to regulate Ca 2+ signaling in N. plumbaginofolia protoplasts. 20 In addition, it has been reported that self-incompatibility is associated with the level of cAMP in pistils after pollination, and the level of cAMP depends on AC activity.…”
Section: Discussionmentioning
confidence: 99%